The Influence of Abrahamic Faiths in the Religious Pluralism Agenda in Malaysia - Rahim Kamarul Zaman; Mujahid Mohammad Fadzil; Hamid Fahmy Zarkasyi (RABBANICA - Journal of Revealed Knowledge, 2024)
Pluralism is a school of thought that originated in the West. It evolved from the ideas of Liberalism, which advocates for unlimited freedom. Pluralism suggests that truth is relative, not absolute. It allows anyone to claim the truth, even without proof. Religious pluralism stems from this concept, asserting that every religion holds truth even if it contradicts the other. In Malaysia, debates over pluralism have led to discussions about Islam being the final revealed religion, preceding Judaism and Christianity. This claim aims to justify Judaism and Christianity as religions revealed by God by classifying all three as part of the Abrahamic Faiths. Consequently, Jews and Christians are also asserted to have a place in heaven. To address this, the study critically analyses these claims and their relationship with the concept of Pluralism. Using the descriptive content analysis method, this qualitative study examined how the doctrine of Abrahamic Faiths and hermeneutic interpretation influence the agenda of religious pluralism in Malaysia. The study’s findings indicated that Religious Pluralism, especially within the framework of the Abrahamic Faiths, is part of an organised international political agenda under the global network of Liberalism. In conclusion, defending the sanctity of Islam from the influence of religious pluralism should be the primary focus of Islamic religious authorities in Malaysia.